2011
DOI: 10.1002/hfm.20252
|View full text |Cite
|
Sign up to set email alerts
|

Personnel selection based on intuitionistic fuzzy sets

Abstract: One of the most important activities carried out by human resource management is personnel selection, concerned with identifying an individual from a pool of candidates suitable for a vacant position. Traditionally, personnel selection is a group decision-making problem under multiple criteria containing subjectivity, imprecision, and vagueness, which are best represented with fuzzy data. In this article, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method extended to intuitionis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…Based on the collective weights of criteria w j , the normalized subjective weight of each criterion is obtained by Equation (10) [32,60].…”
Section: The Proposed Supplier Selection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the collective weights of criteria w j , the normalized subjective weight of each criterion is obtained by Equation (10) [32,60].…”
Section: The Proposed Supplier Selection Methodsmentioning
confidence: 99%
“…To validate the effectiveness of the method being proposed, the intuitionistic fuzzy TOPSIS (IF-TOPSIS) suggested by Boran et al [60] is applied for the given case study. With the use of the evaluation of criteria weights and the ratings of alternative suppliers in Tables 3 and 4, the four alternatives are ranked as A 2 A 3 A 4 A 1 .…”
Section: Criteria Decision Makersmentioning
confidence: 99%
“…Lin (2010) combined ANP and fuzzy data envelopment analysis (DEA) to select personnel. Boran, Genç and Akay (2011) applied Intuitionistic fuzzy TOPSIS to select a sales manager in a manufacturing company. Keršulienė and Turskis (2011) integrated the principles of fusion of fuzzy information, additive ratio assessment method with fuzzy numbers and step-wise weight assessment ratio analysis technique to select architect.…”
Section: Personnel Selection Backgroundmentioning
confidence: 99%
“…Their method was done in group decision making environment. Boran et al (2011) employed an intuitionistic fuzzy TOPSIS approach to select appropriate personnel from candidates when selecting a sales manager at a manufacturing company. Finally Kelemenis et al (2011) for manger selection suggested using Fuzzy TOPSIS.…”
Section: Fuzzy Topsismentioning
confidence: 99%
“…Yeh (2003) and Cheng (2009, 2009a) used interviewing for criteria selection. (Liang and Wang, 1992) Personnel placement (Liang and Wang, 1994) Personnel Selection (Yaakob and Kawata, 1999) Finding the better worker for production line (Ertugrul Karsak, 2000) Personnel Selection for an expatriate position (Lovrich, 2000) Senior economic and financial analyst selection (Chen, 2000) System analysis engineer selection in a software company • (Karsak, 2001) Personnel Selection (Capaldo and Zollo, 2001) Personnel Selection • (Lazarevic, 2001) Senior economic and financial analyst • (Butkiewicz, 2002) Staff selection in a tourism agency (Huang, et al, 2004) Middle manager Selection • (Drigas, et al, 2004) Unemployed Matching (Chen and Cheng, 2005) IS personnel for the position of a project manager • • (Saghafian and Hejazi, 2005) University professor hiring • • (Wang and Elhag, 2006) System analysis engineer selection in a software company • (Golec and Kahya, 2007) Employee evaluation and Selection • (Baykasoglu, et al, 2007) Project team members Selection (Mahdavi, et al, 2008) System analyst selection in a software company Zavadskas et al, 2008) Project manager selection (Canós and Liern, 2008) Personnel selection (Celik, et al, 2009) Recruitment of senior lecturer • Select an overseas marketing manager • (Güngör, et al, 2009) New position personnel selection Dejiang, 2009) RandD personnel selection (Polychroniou and Giannikos, 2009) Credit officer • (Dursun and Karsak, 2010) Industrial engineer • ( Kelemenis and Askounis, 2010) Top management team member • • (Kelemenis, et al, 2011) Manger selection • • (Boran, et al, 2011) Selecting a sales manager at a manufacturing company • (Abbas Rashidi, et al, 2011) Selection of Construction Project Managers • (Zhang and Liu, 2011) H...…”
Section: Selection Criteriamentioning
confidence: 99%